Corticospinal tract involvement in a patient with 3-HMG coenzyme A lyase deficiency - EKİNCİ, GAZANFER (ELSEVIER SCIENCE INC, 2006)
3-Hydroxy-3-methylglutaryl coenzyme A lyase deficiency, an inborn error of ketone body synthesis and leucine degradation, is a rare disorder. There are few reports demonstrating clinical and neuroradiologic findings of this condition. This report describes a 3.5-year-old previously healthy male who was admitted with complex partial seizures and was diagnosed as having 3-hydroxy-3-methylglutaryl coenzyme A lyase deficiency. The patient's previous medical history was unremarkable. His development and neurologic examination were normal. Cranial magnetic resonance imaging indicated prominent corticospinal tract and pontine involvement with focal cerebral white matter changes which have not been described in the literature before. (c) 2006 by Elsevier Inc. All rights reserved.
Keywords: SYRUP-URINE-DISEASE; CEREBRAL-CORTEX; YOUNG-RATS; LEUCINE; 3-HYDROXY-3-METHYLGLUTARYL-COENZYME; MRI